2006
DOI: 10.1016/j.jcrs.2005.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Thermal study of bare tips with various system parameters and incision sizes

Abstract: Microincision lens removal can be performed at safe temperatures with the knowledgeable selection of surgeon-controlled parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 10 publications
0
29
0
2
Order By: Relevance
“…To compensate for these limitations, bimanual phacoemulsification incisions use tighter wound geometry, which may cause oar locking and, thus, difficult intraocular manipulations. 5 Tsuneoka et al 12 suggest small incisions pose a greater risk that phaco tip movement will produce corneal deformation, excessive stromal hydration, and clouding around the incision. Although theoretically smaller wounds intuitively self-seal more easily, this holds true only if the wound morphology and integrity are maintained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To compensate for these limitations, bimanual phacoemulsification incisions use tighter wound geometry, which may cause oar locking and, thus, difficult intraocular manipulations. 5 Tsuneoka et al 12 suggest small incisions pose a greater risk that phaco tip movement will produce corneal deformation, excessive stromal hydration, and clouding around the incision. Although theoretically smaller wounds intuitively self-seal more easily, this holds true only if the wound morphology and integrity are maintained.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques use tighter wound geometry, which may give rise to ''oar locking'' and thus lead to difficulties in intraocular manipulations. 5 At times, such geometry adds stress to the incision, leading to wound distortion, corneal hydration, and thermal injury. Furthermore, a hard nucleus, excessive phaco energy, reduced irrigation, and blockage of flow due to ophthalmic viscosurgical devices increase the probability of damage to the incision.…”
mentioning
confidence: 99%
“…Studies have evaluated the thermal impact of a vibrating needle. [1][2][3][4][5] Several assessed incision temperature using a bare ultrasound tip. [6][7] Others show the benefits of reducing delivered thermal energy by using various surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies revealed that the phaco needle generates heat along its entire length [6][7][8][9] ( fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%